A Simple Equation to Predict a Subscore's Value. Issue 3 (September 2014) - Feinberg, Richard A.; Wainer, Howard
<x xml:space="preserve">Abstract</x> Subscores are often used to indicate test‐takers' relative strengths and weaknesses and so help focus remediation. But a subscore is not worth reporting if it is too unreliable to believe or if it contains no information that is not already contained in the total score. It is possible, through the use of a simple linear equation provided in this note, to determine if a particular subscore adds enough value to be worth reporting.